Tren Teknologi Digital pada Pendidikan Matematika: Analisis Bibliometrik Menggunakan VOSViewer - Naja, Afina Fidaroin; Al Farabi, Muhammad (Universitas Negeri Gorontalo, 2025)
The utilization of digital technology in mathematics education can have a positive impact on efficiency, accessibility, creativity, and collaboration in mathematics learning. This study aims to identify the dynamics of digital technology article publications in mathematics education, the most frequently referenced articles, journals that have the most publications of related articles, and publication mapping in international scientific journals with Google Scholar database. The method used is bibliometric analysis with the research population including 999 articles obtained through the Publish or Perish (PoP) application in the 2014-2024 time span. The collected data were saved in CSV and RIS formats to be analyzed using VOSviewer software. The results showed that the publication trend of articles related to digital technology in mathematics education has increased significantly since 2020 and reached its peak in 2021. Mapping analysis with VOSviewer revealed seven main topics related to digital technology in mathematics learning, namely “ability”, “augmented reality”, “application”, “computational thinking”, “higher education”, “information”, and “systematic review”. These topics are still rarely researched, so they can be an opportunity for further research in the future.